Addressing competency gaps for vocational instructor through competency model and instrument for competency measurement - Arifin, Muhammad Aiman; Mohd Rasdi, Roziah (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
The purpose of this paper is to comprehend the competency, competency models and measurement instruments at workplace settings, its significance to human resource development in terms of knowledge, skills and abilities. Interest on competency based approaches is growing. In the management literature, the competency based approach has grown through McClelland (1973) seminal paper “testing for competencies rather than intelligence” as to argue the traditional approach to measure performance using aptitude and content test. Evidence had also indicated that competency can lead to effective job performance. The practice of competency base approach has resulted with the expansion of models on measurement instrument. This paper discusses the previous competency literature with greater interest on the field of competency, competency models and measurement instruments towards technical vocational education and training in Malaysia specific for vocational college teaching profession. This study suggests that competency modelling and measurement instruments can contribute to the effectiveness of Vocational College Teacher education and to address competency gaps issues. Competency modelling and instruments to measure for vocational teaching is still is in its infancy however the lack of competent teachers is a challenge for Malaysia to reach a better income levels in future.